Seasonal variations of nitrous oxide in a populous urban estuary and its adjacent sea - Tseng, Hsiao-Chun; Yuh Han, Yokie Tai; Lin, Chia-Chia; Gong, Gwo-Ching (Frontiers in Earth Science, 2023)
The first investigations of seasonal N2O variations and water-to-air fluxes in the Tamsui River estuary and its adjacent sea were carried out in this study. In the Tamsui River estuary, the concentration of N2O decreased with increasing salinity. The seasonal variations of N2O concentrations in the estuary were 46.8–148.5 nM in autumn, 15.9–82.5 nM in spring, 11.0–42.0 nM in summer and 13.1–120.6 nM in winter. When salinity regressed to zero, N2O concentration was highest in autumn, followed by winter, spring, and summer, which might be influenced by the DO and NO3- concentrations as well as temperature. Because of mountains occlusion, the seasonal variations in wind speed were not large in the Tamsui River estuary. Seasonal variations of N2O fluxes in the estuary were 10.9–35.6 µmol m-2 d-1 in autumn, 2.8–15.1 µmol m-2 d-1 in spring, 2.4–9.5 µmol m-2 d-1 in summer and 2.7–26.8 µmol m-2 d-1 in winter. In the adjacent sea of Tamsui River estuary, seasonal average N2O concentrations in the surface seawater were 10.3±0.2 nM in autumn, 11.6±1.2 nM in spring, 11.4±0.7 nM in summer and 13.8±0.9 nM in winter, with no significantly seasonal changes while wind speed varied greatly seasonally. Seasonal variations of average N2O fluxes in Tamsui River estuary’s adjacent sea were 40.3±0.7 µmol m-2 d-1 in autumn, 19.7±2.1 µmol m-2 d-1 in spring, 20.9 ± 1.3 µmol m-2 d-1in summer and 49.0±3.3 µmol m-2 d-1 in winter. As a result, seasonal variations in N2O fluxes in the estuary were dominated by N2O concentrations in the water, whereas in the sea, it was dominated by wind speed. Overall, the Tamsui River estuary and its adjacent sea were net sources of atmospheric N2O with annual average fluxes 10.6±6.7 and 32.5±14.5 µmol m-2 d-1, respectively.